The correlation between the levels of fluoride, CaCO3, and pH in clean well water with the calculus index - Amalia, Sheila; Sudarmadji; Qaimamunazzala, Hayu (Universitas Gadjah Mada, 2024)
Background: The fluoride, CaCO3, and pH levels in clean well water are chemical requirements that must be considered to ensure water quality. In terms of dental and oral health, fluoride, CaCO3, and pH in clean well water can increase the risk of dental calculus. Dental calculus contributes to the prevalence of periodontal diseases due to bacteria and plaque. Objective: This study aims to determine, analyze, and explain the correlation between the levels of fluoride, CaCO3, and pH in clean, well water that is consumed among the people of Wukirsari Ward, Imogiri Subdistrict, Bantul Regency, the Special Region of Yogyakarta with the calculus index. Methods: This is an analytical observational study with a cross-sectional design. The subjects were 169 individuals aged between 20 and 44 years who consumed well water. Primary data were obtained directly from interviews, assessments of the calculus index, and measurements of the chemical parameters of water quality. Meanwhile, secondary data were obtained from Imogiri 1 Community Health Center. Data were analyzed using univariate, bivariate, and multivariate analyses with multiple linear regression. Results: Results showed significant variations in moderate fluoride levels, hard CaCO3, and alkaline pH. The predominant correlation was found between low fluoride levels, high CaCO3 levels in clean well water, and age with the calculus severity index. Conclusion: CaCO3 levels in clean well water were the most strongly correlated variable and stood out as a key factor. A potential solution includes increasing fluoride levels by drinking water fluoridation and reducing CaCO3 levels by boiling water. Education about water quality and dental hygiene is key to reducing the prevalence of periodontal diseases and improving public health.